Insecticidal activity of phenylpropanoids from Piper sarmentosum and their interactions with glutathione S-transferase from adult mosquitoes - Hematpoor, Arshia; Asib, Norhayu; Liew, Sook Yee; Lee, Vannajan Sanghiran; Ngadni, Muhammad Afiq (Elsevier B.V., 2025)
This study investigated the insecticidal activity of three phenylpropanoids—asaricin (1), isoasarone (2), and trans-asarone (3)—isolated from the aerial parts of Piper sarmentosum against adult mosquito vectors: Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus. Bioassay-guided fractionation of the plant's hexane extract led to the isolation of these phenylpropanoids. Compounds 1 and 2 exhibited strong adulticidal effects against Aedes species, with LD₅₀ values ≤ 8.8 µg/mL and LT₅₀ values ≤ 29 min. Meanwhile, Culex quinquefasciatus was less susceptible to these compounds, showing LT₅₀ values ≤ 56 min. In contrast, compound 3 showed moderate toxicity across all species. To explore the potential resistance mechanism, glutathione S-transferase (GST) activity was measured and found to correlate positively with the LD₉₅ values of the compounds. Mosquitoes exposed to all isolated phenylpropanoids at LD₉₅ levels showed a significant increase in GST activity, suggesting its involvement in detoxification. Molecular docking studies further confirmed this interaction, revealing consistent binding of all three compounds to key residues (PRO11, GLU64, SER65, ARG66, and TYR105) within the GST active site. Despite increased GST activity—a known marker of metabolic resistance— compounds 1 and 2 remained highly effective, indicating that their mode of action may overcome or bypass common resistance pathways. These findings highlight the potential of P. sarmentosum-derived phenylpropanoids as promising botanical insecticides and underscore the importance of understanding enzyme-ligand interactions in developing effective mosquito control strategies.